A green dual-phase carbon-silica nanohybrid derived from black liquor lignin for reinforcing styrene-butadiene rubber. (10th November 2022) - Jiang, Can; Shen, Huahao; Bi, Xiaoyun; Wang, Zuhao; Yao, Manzhao; Wu, Yanguang; Zhang, Liqun; Yu, Peng
Abstract: In rubber industry, lignin has been investigated as a potential alternative of fossil-derived carbon black (CB) for several decades. However, due to poor dispersity, big particle size and incompatibility with rubber, lignin cannot achieve the same reinforcing effect as CB by direct dry mixing. Here, a new and green dual-phase carbon-silica nanohybrid (LDPCS) was successfully prepared from black liquor lignin (BLL) and sodium silicate through a simple co-gelation/self-assembly and carbonization process. The preparation mechanism and process as well as the morphology and properties of LDPCS were investigated and discussed in detail. The results indicated that the hydroxymethylation and silane modification of BLL could improve its affinity with SiO2 sols, thus facilitating the co-gelation of BLL and SiO2 sols to inhibit the growth of SiO2 particles. During subsequent acid precipitation, silane modified hydroxymethylated BLL (SiHM-BLL) was self-assembled around SiO2 particles to form nanosized SiHM-BLL-SiO2 hybrids. After carbonization, SiHM-BLL-SiO2 nanohybrids were converted into LDPCS with small primary particle size of 60–90 nm, high specific surface area of 82.19 m 2 /g, relatively loose secondary aggregation structure and graphitic microcrystals in the carbon framework. With incorporating LDPCS into styrene-butadiene rubber (SBR) by direct dry mixing, LDPCS showed a superior reinforcing capability for SBR as compared with CB, which was ascribed to the nanoscale dispersion of LDPCS, robust C/SiO2 interfaces and high affinity with SBR matrix. This work provided a new insight into the fabrication of novel hybrid nanofiller from lignin and broadened the potential applications of lignin in rubber compounds and beyond. Graphical abstract: Image 1 Highlights: A green C/SiO2 dual-phase (LDPCS) nanofiller was prepared from black liquor lignin. LDPCS was prepared by a simple co-gelation/self-assembly and carbonization process. LDPCS showed a high specific surface area of 82.19 m 2 /g and C/SiO2 mass ratio of ∼1. LDPCS/SBR compounds had a superior performance to that of CB/SBR compounds.